In Situ Generation of Poly(3,4‐ethylenedioxythiophene)/Ag2SeO3 Nanohybrids at Hexane/Water Interface for Photodegradation of Organic Dyes - Anusree V. Rethnakumaran; Mini Mol Menamparambath (Macromolecular Materials and Engineering)
Abstract Liquid/liquid interfacial synthesis offers a more energy‐efficient alternative to traditional solid‐state reactions, primarily due to its adaptability to low‐temperature and pressure conditions. In the present work, this innovative approach is explored to generate silver selenites within a conducting polymer matrix in an in situ manner. Therefore, a hexane/water interface is employed for the synthesis of Ag2SeO3 on PEDOT support under ambient temperature and pressure conditions. Furthermore, the influence of con. H2SO4 on the polymerization of 3,4 – ethylenedioxythiophene and the regeneration of Ag2SeO3 during polymerization is strategically investigated by ranging the compositions of the precursors. The X‐ray diffraction patterns proved the highly crystalline nature of the nanohybrids with intense peaks attributed to the crystalline Ag2SeO3 attached to PEDOT. The successful formation of the PEDOT/Ag2SeO3 nanohybrids is also confirmed through Raman spectroscopy, FT‐IR, and X‐ray photoelectron spectroscopic techniques. Additionally, SEM images and elemental composition studies verified the morphology and uniform distribution of nanoparticles within the polymer matrix. The efficiency of the liquid/liquid interface in tuning the optical properties, including the band gap tuning of the PEDOT/Ag2SeO3 nanohybrids is verified using UV–vis absorbance and photoluminescence characterizations. The optimized PEDOT/Ag2SeO3 nanohybrid demonstrated enhanced photocatalytic activity for the degradation of rhodamine B (RhB) and methylene Blue (MB), indicating their potential for real‐life applications.